PERBANDINGAN EFEKTIVITAS INFUSA DAN REBUSAN DAUN LANGSAT (Lansium domesticum L) DALAM MENURUNKAN KADAR GLUKOSA SECARA IN VITRO - Nafila nafila; Hayatush Shalihah; Amanah amanah; dian nurmansyah (LPPM Universitas Abdurrab, 2022)
Langsat leaf (Lansium domesticum L) is one of the medicinal plants that can treat diabetes. Diabetes Mellitus is a disease characterized by an increase in blood sugar. Compounds contained in langsat leaves that function to lower blood glucose levels are flavonoids. Flavonoids are protective against damage to cells that produce insulin and can restore insulin receptor sensitivity on cells and even increase insulin sensitivity. This study aims to determine the difference in decreasing glucose levels in vitro with the addition of infusion and decoction of langsat leaves. Glucose levels were measured in vitro using a UV-Vis Sfektorfotometer using the Nelson Somoghy method. The results of the phytochemical screening test showed positive flavonoid compounds, alkaloids, tannins and saponins. The results of data analysis using the Independent T test obtained p-value 0.032 < 0.050. It can be concluded that there is a significant difference in the measurement of glucose levels in vitro with the treatment of infusion and decoction.